Home advantage in the top Czech hockey league - Pelloneová, N. (Studia Sportiva, 2023)
Home advantage in sport has long been established as an important factor in determining the outcome of a match. According to this phenomenon, the home team should win more games and score more goals than the away team. Home advantage is a very complex phenomenon that is influenced by many different factors. One possible explanation is that the home crowd supports the home team's performance and also causes the referee to be under pressure and favor the home team. The aim of this paper is to quantify the home advantage in the Czech top hockey league. Using statistical analysis, the number of points scored, goals scored, shots taken, penalties awarded and penalty minutes in the 2019/20 season were compared. A total of 364 matches were analysed. The results showed the existence of a home advantage in the Czech top hockey league in the 2019/20 season. Implications for sport practice and possible directions for future research are discussed.